Economics, institutions and adaptation to climate change - Christoph Oberlack; Bernhard Neumärker (University of Freiburg, Institute for Economic Research, Department of Economic Policy and Constitutional Economic Theory, 2011)
Adaptation to the consequences of climate change has attracted increasing interest as a necessary complement to greenhouse gas mitigation. Economic approaches to climate adaptation are rarely articulated and discussed explicitly despite many benefits of such a framework-level discourse. Therefore, this article investigates how climate adaptation is framed and approached in economics and attempts to contribute to the development of economic frameworks of climate adaptation. First, the paper identifies and critically reviews four major strands of current adaptation economics: estimation of adaptation benefits and costs, strategies for adaptation, the role of markets and governments, and policy instruments for adaptation. While having their merits, serious methodical difficulties prevail. Moreover, the applied neoclassical framing seems too narrow to capture the plethora of governance challenges and normative criteria revealed in adaptation policy discourses and in the multidisciplinary adaptation literature. The second part of this article outlines an institutional economics approach to climate adaptation that addresses caveats in the current state-of-the-art and offers additional concepts to study climate adaptation. Moreover, promising methods and strategies for adaptation research are presented and future research directions suggested. Finally, the paper assesses the normative foundations of climate adaptation economics and their implications for positive adaptation research.
Keywords: B52; D02; D63; D78; Q54; 330; Economics of Climate Change Adaptation; Institutional Economics; Governance of Climate Adaptation; Adaptive Capacity; Barriers; Normative Economics